Angioedema Hereditário: da manifestação precoce ao diagnóstico e tratamento - Martignoni, Luciane (2022)
Hereditary angioedema (HAE) is an autosomal dominant genetic disorder with immunological repercussions, characterized by subcutaneous and submucosal edema, mainly affecting the extremities, face and abdomen. A condition still underdiagnosed, causing recurrent consultations. The main problems faced by patients and their families are delayed diagnosis and the risk of laryngeal obstruction and event with mortality estimated at 25 to 40%. On average, the diagnosis of HAE occurs around four to seven years after the onset of symptoms. Its pathophysiology based on the quantitative or qualitative alteration of the complement system C1, causing an increase in bradykinin, which, when binding to the B2 receptor, increases the capillary permeability of blood vessels, resulting in angioedema. The objective of this work was to describe the clinical case of an infant who started HAE symptoms at the age of 18 months and to evaluate the peculiarities inherent to the diagnoses in this age group, as well as the evolution and impact on the quality of life. Study of the “case report” type. The review was based on the following outcomes: epidemiology, signs and symptoms/diagnosis and pharmacological treatment. Despite being a non-systematic review, search strategies based on MESH and the use of Boolean operators were employed. The database was Medline/PubMed, using original studies and guidelines, selected according to the convenience of the topic and evaluated by peers. The assertive diagnosis of HAE brought adequate guidance and therapy to the patient who suffered from recurring breaks of edema on the face, lips and abdominal pain since the age of eighteen months. Regarding the review, there is a scarcity of epidemiological studies on HAE, showing that signs and symptoms begin even before the age of ten, with limiting and recurrent abdominal pain being a common clinical finding. The topographic distribution of the disease follows an order of prevalence, being hands(74%), feet (59%), gastrointestinal tract (58%) and face (50%). The severity of the disease accompanies advancing age and the earlier the manifestations, the greater the severity. Child pharmacological treatment has two therapeutic lines, prophylactic (short and long term) and in the acute crisis. First-line prophylactic treatment consists of human plasma-derived C1-INH concentrates and kallikrein inhibitors. Above 12 years old, adult medication are adopted. In the acute crisis conditions, only two drug classes are approved in Brazil: pdC1-INH and icatibant. Few studies were observed in the pediatric population, especially in the therapeutic question, there are minimal clinical trials directed to this population. From the review realized, it was possible to understand the natural history of the disease, as well as the main difficulties faced: diagnosis and early treatment. This study may contribute to the inclusion of HAE in the diagnosis hypotheses of pediatric practice and thus increase the diagnostic and therapeutic probability, in addition to adequate genetic guidance for the family, of this important morbidity still neglected by health professionals.